The exposure to Trichilia catigua (catuaba) crude extract impairs fertility of adult female rats but does not cause reproductive damage to male offspring - Santos, Alice Hartmann dos; Ramos, Aline Camargo; Silveira, Kennia Moura; Kiss, Ana Carolina Inhasz [UNESP]; Longhini, Renata; Diniz, Andréa; Mello, João Carlos Palazzo de; Gerardin, Daniela Cristina Ceccatto (Elsevier B.V., 2015)
Ethnopharmacological relevance: Trichilia catigua is broadly used in folk medicine due to its mental and physical tonic activities and stimulant effects. In animal models, its antidepressant-like effects have been associated with the dopaminergic (DA) system modulation, which has an important role on maternal behavior and male offspring reproductive development.Aim of the study: Since little is known about the adverse effects of the exposure to T. catigua crude extract (CAT) in rats, specially regarding maternal homeostasis and offspring development, the aim of the present study was to evaluate whether CAT exposure may influence maternal toxicity parameters and behavior or disrupt male offspring physical and reproductive development.Material and methods: Dams were treated daily (by gavage) with 400 mg/kg of CAT or vehicle (control=CTR) throughout pregnancy and lactation. Fertility and maternal behavior tests were conducted in dams. Male offspring reproductive and behavioral parameters were analyzed.Results: Dams exposed to CAT showed increased pre- and post-implantation losses rates when compared to CTR group. No significant changes regarding maternal behavior or male offspring parameters were observed.Conclusion: In conclusion, maternal exposure to CAT interfered with implantation during the initial phases of pregnancy but did not induce changes on maternal behavior or male offspring reproductive and behavioral parameters.
Keywords: Trichilia catigua; Fertility; Embryotoxicity; Maternal behavior; Dopamine